PAM: Decision Support for Long-Term Palmer Amaranth (Amaranthus palmeri) Control - Lindsay, K.; Popp, M.; Norsworthy, J.; Bagavathiannan, M.; Powles, S.; Lacoste, Myrtille (Weeds Science Society of America, 2017)
© Weed Science Society of America, 2017. Palmer amaranth is the most troublesome weed problem in mid-southern US crop production. Herbicides continue to be the most commonly employed method for managing Palmer amaranth, despite the weed's widespread resistance to them. Therefore, farmers need research and extension efforts that promote the adoption of integrated weed management (IWM) techniques. Producers, crop consultants, educators, and researchers would be more likely to deploy diversified chemical and nonchemical weed management options if they are more informed about long-term biological and economic implications via user-friendly decision-support software. Described within is a recently developed software that demonstrates the effects of Palmer amaranth management practices on soil seedbank, risk of resistance evolution, and economics over a 10-year planning horizon. Aiding this objective is a point-and-click interface that provides feedback on resistance risk, yield potential, profitability, soil seedbank dynamics, and error checking of management options. Nomenclature: Palmer amaranth, Amaranthus palmeri S. Wats.